2018
DOI: 10.3389/fmicb.2018.03145
|View full text |Cite
|
Sign up to set email alerts
|

Demethylmenaquinone Methyl Transferase Is a Membrane Domain-Associated Protein Essential for Menaquinone Homeostasis in Mycobacterium smegmatis

Abstract: The intracellular membrane domain (IMD) in mycobacteria is a spatially distinct region of the plasma membrane with diverse functions. Previous comparative proteomic analysis of the IMD suggested that menaquinone biosynthetic enzymes are associated with this domain. In the present study, we determined the subcellular site of these enzymes using sucrose density gradient fractionation. We found that the last two enzymes, the methyltransferase MenG, and the reductase MenJ, are associated with the IMD in Mycobacter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…The classical MK biosynthesis pathway ( Fig. 1A) starts with the synthesis of the naphthoquinone headgroup precursor (1,4dihydroxy-2-naphthoic acid (DHNA)) in the cytosol (22,23), followed by prenylation and methylation by membrane-bound enzymes to produce the lipid-soluble MK (24,25). In addition to its electron transport role, the prenyl tail of MK can be further modified, and these modified quinones have been shown to regulate virulence of Mtb infection (7,26,27).…”
mentioning
confidence: 99%
“…The classical MK biosynthesis pathway ( Fig. 1A) starts with the synthesis of the naphthoquinone headgroup precursor (1,4dihydroxy-2-naphthoic acid (DHNA)) in the cytosol (22,23), followed by prenylation and methylation by membrane-bound enzymes to produce the lipid-soluble MK (24,25). In addition to its electron transport role, the prenyl tail of MK can be further modified, and these modified quinones have been shown to regulate virulence of Mtb infection (7,26,27).…”
mentioning
confidence: 99%
“…We found that 20 of the 29 proteins were those previously found by the proteomic analysis ( Table 1 ). One of the remaining 9 proteins, MenA (MSMEG_0988), was not listed in our proteome, but we have shown in a separate study that it is a PM-CW-associated protein (25). Therefore, we considered this a false-positive, and did not investigate this protein further.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 20 previously identified IMD proteins, GlfT2, PyrD, MenG and MurG have already been examined by biochemical and fluorescence image analysis (8, 13, 14, 25), establishing the characteristic features of IMD-associated proteins. We chose two proteins, GlfT2 (MSMEG_6403) and PyrD (MSMEG_4198), to confirm that the Dendra2-FLAG tag fusions are biochemically associated with the IMD fraction.…”
Section: Resultsmentioning
confidence: 99%
“…The classical MK biosynthesis pathway ( Figure 1A) starts with the synthesis of the napthoquinone head-group precursor (DHNA) in the cytosol [22,23], followed by prenylation and methylation by membrane bound enzymes to produce the lipid soluble MK [24,25]. In addition to its electron transport role, the prenyl tail of MK can be further modified and these modified quinones have been shown to regulate virulence of the Mtb infection [7,26,27].…”
Section: Mtb-mendmentioning
confidence: 99%